Penguasaan Komunikasi, Disiplin, dan Kerja Sama Melalui Praktik Kerja Industri Bidang Manufaktur oleh Siswa Kelas XII Teknik Pemesinan SMK Negeri 3 Yogyakarta - Teguh Raharjo; Putut Hargiyarto (Department of Mechanical Engineering Education, 2020)
This study aims to determine the communication skills, discipline, and teamwork of students after carrying out industrial work practices in the manufacturing sectors, and to study the implementation of the industrial work practices. The studied subjects are the students of class XII in the engineering expertise program of SMK Negeri 3 Yogyakarta. This research is a combination research type with a sequential explanatory strategy model with quantitative and qualitative data. Data were collected using interviews and documentation. The sampling techniques used are purposive sampling and snowball sampling with a sample of 76 students and one internship supervisor. Data analysis techniques used quantitative descriptive statistics, data frequency distribution, analysis of variable indicators, and qualitative analysis of interview results. The results showed that students' communication ability was classified as